the Comparison of Pixel Size and Anatomy Information of Radiograph Digital Image using DICOM viewer and Whatsapp - Tengku Mohammad Yoshandi; Abdul Zaky; Annisa Mahfuyana (Jurnal Komputer Terapan, 2023)
Technological advancement provides the biggest impact on the administration and information delivery system in hospitals. The adoption of a Paperless policy by hospitals demands that all activities involving information delivery to be done digitally. The availability of relevant media such as smartphones serve to support the adoption of such a policy. Patients who required the services of the Radiology Facility used to be given printed rontgen images to assist their doctors in their diagnosis, but with the emergence of digitalization, the patients are now provided with digital images that are distributed via WhatsApp. Such a method can also be applied to Radiograph interpretation, where information can be delivered remotely through the usage of PACs and/or WhatsApp. The interpretation standard for radiographs utilizes the DICOM Viewer, which means that recent social media developments offer an increased ease of access to the interpretation process by way of WhatsApp. The image that is sent via WhatsApp typically gets compressed, which consequently causes a loss of information in the image. This study aims to compare doctor’s opinions and image quality viewed between WhatsApp and DICOM viewer. This study is a quanitative comparative study through documentation, observation, and data collecting questionnaire. The study found that the image that was sent using WhatsApp suffered a decrease in size and pixel quantity. Therefore, the anatomical information provided by the two radiographs were different.